Clinical utility of liquid biopsy next-generation sequencing for advanced non-small cell lung cancer in the Netherlands - Tessa J. J. de Bitter; Maartje J. Geerlings; Leonie I. Kroeze; Daniel von Rhein; Milou M. F. Schuurbiers; Janne M. Bibbe; Joyce A. M. G. Smeijers; Hicham Ouchene; Christian Gilissen; Tom G. J. Hofste; Marjan M. Weiss; Longkankernet; et al. (Scientific Reports)
Abstract Tumor molecular profiling is essential for therapeutic management of advanced non-small cell lung cancer (NSCLC). However, a biopsy is not for every patient possible and can have complications, which plasma derived circulating tumor DNA (ctDNA) analysis could overcome. We assessed the clinical utility of ctDNA next-generation sequencing (ctDNA-NGS) in 72 NSCLC patients, including 59 who underwent both standard of care (SoC) tissue- or cytology-based genotyping and ctDNA-NGS and 13 who underwent only ctDNA-NGS. Hypothetical shifts in diagnostic yield of a ctDNA-first strategy were modelled using real-world NSCLC molecular testing data from The Netherlands. Concordance between SoC and ctDNA-NGS was 71.2%. In fifteen patients (25.4%) results were discordant, but without direct therapeutic impact. In two patients (3.4%), ctDNA-NGS missed an actionable driver, which would directly impact therapy. Hypothetical shifts in diagnostic yield of a ctDNA-first strategy were determined. This predicted a 7.0% decrease in diagnostic yield for (non-) actionable drivers if all patients underwent ctDNA-NGS, including those currently tested in SoC and those not. Offering ctDNA-NGS only to patients not tested in SoC would increase the diagnostic yield by 6.7%. In conclusion, ctDNA-NGS shows promise for predictive diagnostics in advanced NSCLC, offering added value alongside SoC, but comes with assay-specific and biological challenges.